2018
DOI: 10.1177/0734242x18785722
|View full text |Cite
|
Sign up to set email alerts
|

Municipal solid waste management: Constraints and opportunities to improve capacity of local government authorities of Phnom Penh Capital

Abstract: Solid waste management is a challenge for Phnom Penh city owing to the increasing volume of waste produced and insufficient collection capacity. Sustainable management is required in response to continuing population growth and urbanisation. This article aims to examine the status and constraints of solid waste management in Phnom Penh and discuss the performance of local government authorities to propose possible mechanisms and strategies to improve the system. Data were collected through literature reviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…From 1995 to 2010 and then to 2015, MSW generation in Phnom Penh increased rapidly from 0.136 million tons in 1995 to 0.409 million tons in 2010 [28] and then to 0.681 million tons in 2015 [15,29]. Waste generation rates are affected by socio-economic development, level of industrialization, urbanization, excessive consumption of modern life and climate.…”
Section: Results and Discussion Waste Generation And Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…From 1995 to 2010 and then to 2015, MSW generation in Phnom Penh increased rapidly from 0.136 million tons in 1995 to 0.409 million tons in 2010 [28] and then to 0.681 million tons in 2015 [15,29]. Waste generation rates are affected by socio-economic development, level of industrialization, urbanization, excessive consumption of modern life and climate.…”
Section: Results and Discussion Waste Generation And Compositionmentioning
confidence: 99%
“…The inadequate transportation facilities of CINTRI have necessitated a shift in the collection time and transportation routine from day to night time for some inner city districts and commercial areas. Spoann et al [15] indicated that the collection capacity of CINRTI is limited not only in terms of facilities but also lacks personnel resources. In other words, the main constraint on waste collection is the lack of personnel due to low compensation rates.…”
Section: Waste Collection Transportation and Disposalmentioning
confidence: 99%
See 3 more Smart Citations